2012
DOI: 10.1111/j.1600-0528.2012.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's use of dental services: influence of maternal dental anxiety, attendance pattern, and perception of children's quality of life

Abstract: Use of dental care services by preschool children was low, and treatment was neglected even among children who had visited a dentist. Children of mothers with low schooling level who do not visit a dentist regularly were at greater risk of not receiving dental care. Maternal perception of their child's oral health motivated visits to the dentist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
109
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 25 publications
17
109
2
6
Order By: Relevance
“…Furthermore, maternal patterns of dental attendance may be related to those adopted in their children. The avoidance of dental treatment by mothers creates a worse scenario for their children´s oral health (20). Indeed, a recent study observed that maternal oral health practices from mothers were associated to children's caries prevalence and also that mothers could accurately evaluate their children's oral health (21).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, maternal patterns of dental attendance may be related to those adopted in their children. The avoidance of dental treatment by mothers creates a worse scenario for their children´s oral health (20). Indeed, a recent study observed that maternal oral health practices from mothers were associated to children's caries prevalence and also that mothers could accurately evaluate their children's oral health (21).…”
Section: Discussionmentioning
confidence: 99%
“…Among the children participating in the present study, the prevalence of caries was 51.4%, which is high when compared with data from the Ministry of Health's survey even though this sample included a younger population. Other cross-sectional studies conducted in Brazilian cities also described lower prevalence of dental caries in preschool children than that observed in Ponta Grossa 26,27,28 . However, a striking feature is that, as for Ponta Grossa, these studies also showed that the proportion of filled teeth was very low, even among children who have been to the dentist 26,27,28 .…”
Section: Discussionmentioning
confidence: 64%
“…Adherence to treatment (AT) in children is influenced by many factors, such as age, parental education level, maternal perceptions about dental care, socioeconomic status and dental anxiety (DA) (Edelstein, 2002;Edelstein & Chinn, 2009;Goettems et al, 2012;).…”
Section: Introductionmentioning
confidence: 99%